Use of Carbon Nano-Fibers in Cementitious Mortar - Muhammad Maqbool Sadiq Awan; Parviz Soroushian; Arshad Ali; Muhammad Yousaf Saqid Awan (Universitas Pendidikan Indonesia, 2017)
Cementitious materials, especially those with higher compressive strengths, provide relatively low toughness, tensile strength and strain capacity, and are susceptible to cracking under load and restrained shrinkage effects. These drawbacks were overcome through development of multi-scale reinforcement systems comprising carbon nanofibers and microfibers for high-strength cementitious mortars. Multi-scale reinforcement of the high-performance mortar produced significant gains in the flexural strength and toughness, and abrasion and impact resistance. Microstructural investigations were also conducted in order to provide insight into the structure and failure mechanisms of high-performance cementitious mortars with multi-scale reinforcement.